Cluster analysis for bank customers selection of Islamic mortage financing in Eastern Malaysia: an empirical investigation - Hanudin Amin; Mohamad Rizal Abdul Hamid; Suddin Lada; Ricardo Baba (Emerald, 2009)
Purpose – The purpose of this paper is to explore the reasons behind customers’ selection of Islamic mortgage in Sabah, Malaysia and present factor and cluster analyses to identify the importance of choice criteria for Islamic mortgage selection. The choice criteria among Sabahans are investigated along with their gender, age group, religion, monthly income, and ethnicity. Design/methodology/approach – A total of 250 bank customers responded to a survey addressing the choice criteria for Islamic mortgage providers. It is important to address the criteria in order to make sure the service providers are able to come up with attractive package of Islamic home financing to their prospective customers. Of these, only 211 questionnaires are usable, which gives us a response rate of 84.4 percent. No extra efforts are conducted in order to increase the number of respondents. Non-probability, convenience sampling is implemented. This paper uses a quantitative study similar to what employed by Lymperopoulos et al. and by Devlin. Frequencies, descriptive, factor and cluster analyses are used to analyze the data. Findings – A cluster analysis indicates that bank customers can be divided into three clusters. Members of cluster 1 reported a tendency to select mortgage bank on the basis of “service provisions” while the members of cluster 2 reported a tendency to select mortgage bank on the basis of “elements of Shariah and Islamic principles.” While those of members in the cluster 3, almost entirely had lower mean scores as compared to other clusters. Nevertheless, the members of this cluster reported a greatest tendency to choose Islamic mortgage provider on the basis of “pricing.” Research limitations/implications – The paper has addressed three limitations that provide opportunities for other researchers to explore them in depth in the future in the similar field of Islamic home financing. The limitations are presented in the conclusion’s part. Practical implications – With regard to implications, this paper offers inputs for management decision among Islamic mortgage providers (i.e. Islamic banking institutions such as full-fledged Islamic banks, conventional banks with Islamic windows and conventional banks with Islamic subsidiaries). In addition, this paper adds to the literature in the area of home loans/financing. Originality/value – This paper offers the choice criteria for Islamic mortgage providers provides useful information on the Islamic mortgage providers’ selection among Sabahans. This paper indeed provides useful information on the main choice criteria that affect why Sabahan choose Islamic mortgage providers